Tyrosinase Activity and Anti-Microbial Potential of Cosmos Caudatus Extract - Then, Abegal (2016)
Cosmos caudatus, or known locally as “ulam raja” is a plant popular among Malaysians as a local delight. C. caudatus is believed to have growing potentials in various industries due to its natural anti-oxidant and anti-microbial properties. The undesirable browning effect on mammalian skin cells involves an enzyme tyrosinase and it indicates the aging of skin cells, thus this problem remains an aesthetic skin issue. To date, no studies had been done on the anti-tyrosinase potential of C. caudatus. Thus, this study aimed to determine the total phenolic content (TPC) and total flavonoid content (TFC) in C. caudatus crude leaf extract, to quantify the content of thin layer chromatography (TLC) isolated quercetin (QU) in C. caudatus crude leaf extractas as a tyrosinase inhibitor and as an inhibitory agent against the growth of Staphylococcuss aureus. C. caudatus leaves (3.0 g) were grinded and water was used as the extraction solvent. Two separate assays using Folin-Ciocalteu reagent and 2% (w/v) methanolic aluminium chloride respectively were performed to quantify TPC and TFC. TLC was used to isolate QU from crude extract and QU concentration was determined. C. caudatus crude leaf extract (20 uL) was introduced to tyrosinase in order to assess its inhibition activity. Anti-microbial qualitative screening was done by growing S. aureus on C. caudatus crude leaf extract (250 uL). C. caudatus crude leaf extract contained 12.862 ± 0.04 mg GAE/g of TPC and 5.132 ± 0.04 mg QUE/g of TFC based on fresh leaf weight. Moreover, the TLC-isolated QU from crude leaf extract was 0.110 mg QUE/g based on QU standard curve. The percent (%) tyrosinase inhibition of C. caudatus crude extract, kojic acid and ascorbic acid were 71.98%, 98.08% and 98.83% respectively. Michaelis-Menten parameters, Km and V max of C. caudatus crude extract were 1.05 x 10² mMmin-1 respectively, and for tyrosine, were calculated to be 3.04 x 10-4 mM and 1.42 x 10-2 mMmin-1 respectively. S. aureus colonies grown under presence of C. caudatus crude extract were lesser than that grown on QU control. In conclusions, TPC was higher than TFC due to the presence of various phenolic compounds in crude leaf extract of C. caudatus. The lowest % tyrosinase inhibition (71.98%) and higher Km (1.05 x 10-2 mM) of C. caudatus crude extract might suggest lack of its selectivity towards tyrosinase compared to other inhibitors such as kojic acid and ascorbic acid as well as tyrosinase’s substrate, tyrosine.